2012
DOI: 10.5604/15093492.1012504
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body posture of women and men over 60 years of age

Abstract: 1. There are significant changes in body posture of women and men over 60 years of age both in the frontal and sagittal plane. 2. Men over 60 years of age have a significantly greater angle of lumbar lordosis. 3. The results of these studies should be used for the construction of a plan of exercises for the elderly taking into account all the changes that occur with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 18 publications
3
34
0
2
Order By: Relevance
“…A study evaluating the body posture of men and women over 60 years of age by a non-invasive photogrammetric method also revealed opposite findings. According to their study, men had higher LLA than women [27].…”
Section: Discussionmentioning
confidence: 95%
“…A study evaluating the body posture of men and women over 60 years of age by a non-invasive photogrammetric method also revealed opposite findings. According to their study, men had higher LLA than women [27].…”
Section: Discussionmentioning
confidence: 95%
“…Pod sta wa fi zycz na tych zja wisk no si w opty ce nazwę zja wi ska Mo ire'a. Ba da nie wy ko na no we dług za le ceń po da nych przez pro du cen ta [8,9]. Na pod stawie uzy ska nych fo to gra mów do ko na no ana li zy posta wy cia ła w opar ciu o ozna czo ne wcze śniej punk ty an tro po me trycz ne i wy zna czo no na stę pu ją ce pa rame try opi su ją ce po sta wę cia ła:…”
Section: Methodsunclassified
“…In optics, the physical basis for these phenomena is called the Moire effect. The tests were performed accordingly to the producer's instruc tions [8,9]. On the basis of the obtained photogrammes, relying on previously marked antropo metric points, we performed body posture analysis and mapped the following parameters that characterize body posture:…”
Section: Methodsmentioning
confidence: 99%
“…However, such changes start with a slow progression between the ages of 40-50 years and increase mainly after 60 years of age. 53,54 Large studies have reported marked postural changes occurring in men and women, above 59 and 60 years of age respectively. 54,55 The selection of patients through a single upper limb unit overseen by an orthopaedic surgeon could have caused selection bias (spectrum bias) depending on the chosen clinical tests as well as accuracy and expertise in performing the tests.…”
Section: Methodological Considerations and Study Limitationsmentioning
confidence: 99%